Revisiting interest rate and lending channels of monetary policy transmission in the light of theoretical prescriptions - Abdul-Aziz Iddrisu; Imhotep Paul Alagidede (Central Bank Review (CBR), 2020)
Although theories on channels of monetary policy transmission emphasize indirect monetary policy effect on inflation and output, empirical literature is surprisingly rooted in a direct approach. The use of variants of vector autoregression, with theoretical ordering of variables, does not only fail to quantify the indirect effect, but are also fraught with disagreements on identification of shocks of monetary policy. We revisit the interest rate and lending channels of monetary policy transmission in an approach that is grounded in theory and elicits step-by-step transmission of monetary policy impulses and the eventual effect on inflation in South Africa. We find interest rate and lending channels to be operative in South Africa. For the interest rate channel, a percentage restriction in monetary policy increases lending rate by 0.29%; a percentage increase in the lending rate reduces investment by 0.063%; and a percentage fall in investment reduces inflation by 0.074%. For the lending channel, a percentage restriction of monetary policy reduces banking sector credit by 0.22%; a percentage fall in private sector credit reduces investment by 0.20%; and a percentage decline in investment reduces inflation by 0.086%. These results are robust to different samples and specifications.
Keywords: 330; Inflation; Monetary policy; Three-stage least square; Transmission channels